Peran Pemerintah Daerah dalam Implementasi Undang-Undang Desa - Julian Fahira; Ridho Agustinus Harianja; Fitri Akbar (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
This research examines the role of local government in implementing the Village Law. In the context of village government, the role of local government is important to facilitate and support the implementation of village policies regulated by the Village Law. This paper aims to analyze the legal framework governing the role of local governments, identify the factors that influence their role, and describe the challenges and constraints faced by local governments in carrying out their roles. In addition, this article also provides strategies and solutions that can be implemented by local governments in overcoming these challenges. Through this research, we use a descriptive-analytical method to analyze relevant laws and regulations, and conduct a literature review regarding relevant case studies and empirical research. We found that the role of local government is very important in facilitating and supporting village governance. However, there are several challenges faced, including institutional, financial, HR, and infrastructure constraints. To address this challenge, close collaboration between local government, village government and other stakeholders is essential. Keywords: Local government, Village Law, village government, legal framework.